HUBUNGAN KEBIASAAN BELAJAR SISWA DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - wilda, wilda; Zuardi, Zuardi; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the relationship between study habits and the learning outcomes of the student’s mathematical konowledge in the 5th Grade of all Elementary Schools in Cluster IV of Payakumbuh Barat District, Payakumbuh. This is a correlational research. Sampling was conducted with the saturted sampling technique and the sample includes 5th Grade students in all of Elementary Schools in Cluster IV of Payakumbuh Barat District, Payakumbuh. Data were collected through tests and the hypothesis testing used a product moment correlation formula. Based on the results of the research, it was found that the study habits and the learning outcomes of the 5th Grade students of Elementary Schools in Cluster Iv of Payakumbuh Barat District, Payakumbuh are categorized as moderate. The result of the product moment correlation test shows that tcount (0,954)>ttable (0,177), which means that there is a correlation between study habits anda the learning outcomes of the students’ mathematical knowledge in the 5th Grade of all Elementary Schools in Cluster IV of Payakumbuh Barat District, Payakumbuh.